Fashion, History, Museums Inventing the display of dress - Petrov, Julia (Bloomsbury Academic, 2019)
The last decade has seen the growing popularity and visibility of fashion as a cultural product, including its growing presence in museum exhibitions. This book explores the history of fashion curating and exhibitions, highlighting the continuity of past and present curatorial practices. Comparing and contrasting exhibitions from different museums and decades - from the Paris Exposition Universelle of 1900 to the Alexander McQueen Savage Beauty show at the Metropolitan Museum of Art in 2011 - it makes connections between museum fashion and the wider fashion industry. By critically analyzing trends in fashion exhibition practice over the twentieth and early twenty-first centuries, Julia Petrov defines and describes the varied representations of historical fashion within British and North American museum exhibitions.